The Use of the Write It Arabic Application in Developing the Writing Skill of Beginner Arabic Leaners: A Descriptive Study: استخدام تطبيق Write It Arabic في تنمية مهارة الكتابة لدى متعلمي اللغة العربية المبتدئين: دراسة وصفية - Fahmi, Yahya Tsani; Wahyudi, M. Aldi; Mulyadi, Mulyadi (PT. Student RIhlah Indonesia, 2026)
Effective mastery of Arabic script remains a fundamental challenge for non-native beginners, necessitating the evaluation of digital learning tools. This study aims to describe the Write It Arabic application and explain how it is used to develop writing skills for beginner learners of the Arabic language. The researcher employed a descriptive method by collecting information related to the application’s features, its method of presenting Arabic letters, and the training mechanisms provided to users. The findings indicate that the application offers an appropriate learning environment for beginners, as it presents the form and pronunciation of each letter, followed by a visual demonstration of the steps for writing it, before guiding learners to a practical training stage that relies on direct recognition of handwriting. The results also show that the program provides several useful features, including short lessons, immediate feedback, and the ability to repeat exercises, in addition to assessment tools that help evaluate learners’ proficiency levels. However, the study also identifies several limitations, such as the application’s focus on letters only without progressing to word-level writing, the presence of advertisements in certain versions, and the limited availability of free content. The novelty of this study lies in its specific focus on the mechanical-kinesthetic features of handwriting recognition in Arabic MALL (Mobile Assisted Language Learning). The study concludes that the Write It Arabic application can serve as an effective tool to support the teaching and learning of basic writing skills, both in classroom settings and self-directed learning contexts, provided that further development is undertaken to include higher levels of writing skills.